Dyadic coping in specialized palliative care intervention for patients with advanced cancer and their caregivers: Effects and mediation in a randomized controlled trial. Issue 2 (15th November 2018) - von Heymann‐Horan, Annika; Bidstrup, Pernille Envold; Johansen, Christoffer; Rottmann, Nina; Andersen, Elisabeth Anne Wreford; Sjøgren, Per; von der Maase, Hans; Timm, Helle; Kjellberg, Jakob; Guldin, Mai‐Britt
Abstract: Objective: Specialized palliative care (SPC) interventions increasingly include patient‐caregiver dyads, but their effects on dyadic coping are unknown. We investigated whether an SPC and dyadic psychological intervention increased aspects of dyadic coping in patients with advanced cancer and their caregivers, whether dyad characteristics moderated effects and whether aspects of dyadic coping mediated significant intervention effects on caregivers' anxiety and depression. Methods: We randomized 258 patients with incurable cancer and their caregivers to care as usual or accelerated transition from oncological treatment to home‐based SPC and dyadic psychological support. In secondary outcome analyses, using mixed‐effects models, we estimated intervention effects and 95% confidence intervals (CIs) for communication of stress and common coping, and moderation by dyad type and demographics. In path analyses, we investigated whether stress communication and common coping mediated intervention effects on caregivers' symptoms of anxiety and depression. (Clinicaltrials.gov NCT01885637). Results: The intervention significantly increased common coping in patients and caregivers in couples (estimated difference, 0.68; 95% CI, 0.11 to 1.24) and stress communication by partner caregivers (0.97; 0.24 to 1.24). We found some support for different intervention effects for spouses and other dyads, but no evidence of mediation. Conclusions: Specialized palliative care and dyadic psychological intervention may affect aspects of dyadic coping. Common coping and stress communication did not mediate the previously found significant intervention effects on caregiver anxiety and depression, indicating that other mechanisms may have been central in the intervention.